2016
DOI: 10.1159/000445893
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transfer Protein Syndrome in a Non-Mediterranean Area

Abstract: Background: Plant food allergies associated with lipid transfer protein (LTP) have been widely described in the Mediterranean Basin. Objective: The aim of this work was to describe the clinical profile and pollen sensitization of plant food- allergic patients sensitized to LTP in a non-Mediterranean area. Methods: Patients with clear IgE-mediated symptoms associated with plant foods and a positive skin prick test (SPT) to Pru p 3 were included in a prospective study in the north of Spain. Reported symptoms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
(43 reference statements)
2
31
1
1
Order By: Relevance
“…Our data are the first to indicate that LTP allergy is manifest in UK‐born adults, with sensitization patterns to LTP allergens similar to those seen in matched Italian subjects. The geographical variation in plant food allergies is well reported, but our data add to published evidence that LTP allergy occurs in northern regions of Mediterranean countries and also other regions of Europe . Recent studies include one on Austrian subjects with severe reactions to plant foods, who have been shown to be sensitized to Pru p 3, and a large data set has demonstrated that LTP sensitization is present in subjects living in Belgium .…”
Section: Discussionsupporting
confidence: 75%
“…Our data are the first to indicate that LTP allergy is manifest in UK‐born adults, with sensitization patterns to LTP allergens similar to those seen in matched Italian subjects. The geographical variation in plant food allergies is well reported, but our data add to published evidence that LTP allergy occurs in northern regions of Mediterranean countries and also other regions of Europe . Recent studies include one on Austrian subjects with severe reactions to plant foods, who have been shown to be sensitized to Pru p 3, and a large data set has demonstrated that LTP sensitization is present in subjects living in Belgium .…”
Section: Discussionsupporting
confidence: 75%
“…In the future, these low-allergen WNs could be used for desensitization therapy of patients who are allergic to WNs. LTP allergen (Jug r 3) appears to be one of the candidate allergens causing severe reactions in patients with LTP syndrome, 16 17 but not in this study. In order to draw more definite conclusions on LTP, further studies on older participants are needed.…”
Section: Discussioncontrasting
confidence: 58%
“…Therefore, they served as models for plant food allergy and were extensively studied during the past decades . LTPs are one of the major causes of FA in Mediterranean countries, though some recent studies also suggest LTP sensitization distinct from this geographic location . Their high structural homology gives rise to the LTP‐syndrome, characterized by clinically relevant IgE cross‐reactivity between homologs from various fruits and vegetables .…”
Section: Introductionmentioning
confidence: 99%